(untitled) (International Journal of Sustainable Applied Sciences (IJSAS), 2024)
The purpose of the effects of Artificial Intelligence (AI) on English Proficiency at VIII grade student of MTs DDI Kulo is to provide a dynamic, exciting, and effective learning anvironment that uses cutting-edge to improve student’s English Proficiency.This study employs quantitative techniques as a research strategy. This quantitative study aims to provide strong empirical proof of the benefits of using the Artificial Intelligence (AI) to incrase student’s English Proficiency at MTs DDI Kulo. The use of technology in education has made considerable strides, notably in secondary English language instruction. The purpose of this study is to investigate the use of Artificial Intelligence (AI) as a tool for increasing English proficiency in students at MTs DDI Kulo. The method used was a field experiment with class VIII students as research subjects. Pre-test and post-test asessments, as well as a survey were used to collect information about student’s perceptions of their learning experiences with this technology. The results showed a significant improvement in student’s English proficiency after using Artifical Intelligence (AI) regularly. In addition, the survey also revealed that students felt more motivated and actively engaged in learning English because use this technology. In conclusion, use Artificial Intelligence (AI) can be effective in empowering the English learning process at MTs DDI Kulo. The implications of this study suggest the need for the integration of Artificial Intelligence (AI) technology in education as a means to improve students’s overall learning outcomes.